Matija Murko and Structural Aesthetics - Zelenka, Miloš (Primerjalna književnost, 2025)
At first glance, the connection between the positivist-oriented Murko and structural aesthetics may seem inappropriate and paradoxical. However, his unpublished correspondence with his student, the renowned Czech Slavist and comparatist Frank Wollman (1888–1969), shows the convergence of thematic areas and disciplinary intersections that foreshadowed structural aesthetics. As the editor of Slavia, Murko made it possible for the key figures of Czech structuralism to publish in this journal even before the founding of Slovo a slovesnost (e.g., R. Jakobson, P. Bogatyrev, etc.). At the same time, as the main organizer of the First International Congress of Slavic Philologists in Prague in 1929, he agreed to set up a thematic section in which the theses of the Prague Linguistic Circle were announced. In the first issue of Slavia in 1922–1923, a survey study by Jakobson and Bogatyrev entitled “Slavjanskaja filologija v Rossii za gody 1914–1921” was published. Wollman, who after Murko was to become a candidate for the Chair of South Slavic Languages and Literatures at the Faculty of Arts in Prague, oriented himself towards the study of versology and stylistics, as reflected in his article “Njegošův deseterec” on the evolution of verse forms in the Serbo-Croatian verse (Slavia 1930–31). Murko also encouraged his student to write Slovesnost Slovanů (1928), a pioneering work that focused on the structural history of Slavic literatures as a history of timeless forms and structures.
Keywords: comparative literature; Jezikoslovje; južnoslovansko ljudsko pesništvo; Murko, Matija; Prague linguistic circle; Praški lingvistični krožek; Primerjalna književnost; Slovenian literary historians; slovenski literarni zgodovinarji; South Slavic folk poetry; structural aesthetics; strukturalna estetika; versology; verzologija; Wollman, Frank